Validation of a questionnaire of knowledge and attitudes about the subcutaneous venous reservoir in nursing - Roberto Raña-Rocha; Ignacio López-; María-Jesús M; Carmen Coronado Carvajal (Universidade de São Paulo, 2020)
Objective: design and validate a questionnaire to evaluate the knowledge and attitudes of nurses about the subcutaneous venous reservoir. Method: pilot test: 30 specialized care nurses. Main study: 236 nurses of primary and specialized care. Content validity was evaluated by Lawshe index, reliability by test-retest, internal consistency by Cronbach alpha, and construct validity by exploratory factorial analysis. Results: Items with a Lawshe index lower than 0.51 were eliminated. In the test-retest, the intraclass correlation coefficient was higher than 0.75 for all items. The Cronbach alpha of the attitude questionnaire reached 0.865. The Cronbach alpha value for knowledge was 0.750. The exploratory factor analysis identified a set of four dimensions for each part that explain 64% (attitude) to 80% (knowledge) of variability. Conclusion: the analysis of the reliability and validity of the questionnaire supports its use as an instrument to assess the knowledge and attitudes of nurses towards the subcutaneous venous reservoir.